THE RELATIONSHIP OF WORK ENVIRONMENT TOWARDS EMPLOYEE’S JOB SATISFACTION FOR MILLENNIALS IN JAKARTA - Sabila, Ghaissatika Fairuz; Pritasari, Adita (Journal of Business and Management, 2018)
Abstract. By doing this research, the author wants to examines if the work environment have a relationship towards job satisfaction of millennial employee in Jakarta. The author tried to explore whether work environment would have significant relationship with job satisfaction, in this case work environment that were analyzed are office facility, work flexibility, social relationship, job security, and job esteem. A quantitative survey questionnaire is conducted to explore the relationship between independent and dependent variable. Multi linear regression were applied to analyze the relationship between independent and dependent variable in this study. Based on the data from the sample of 155 millennial employees in Jakarta, work environment that give significant relationship with job satisfaction are Physical office facility and job esteem.Keyword: Work Environment, Job Satisfaction, Office Facility, Social Relationship, Work Flexibility, Job Security, Job Esteem